Mechanical design of electric motors / Wei Tong - Tong, Wei
Provides in-depth knowledge of state-of-the-art design methods and developments of electric motors. From motor classification, design of motor components, model setup, and material and bearing selections to power losses, motor cooling, design integration, vibration, and acoustic noise, this comprehensive text covers the fundamentals, practical design and design-related issues, modeling and simulation, engineering analysis, manufacturing processes, testing procedures, and performance characteristics of electric motors today